Pengaruh Variasi Insulator Saluran Chilled Water Terhadap Performansi Prototype Mini Water Chiller - Buddhi Satya Utama; I Nyoman Pasek Nugraha; I Gede Wiratmaja (Universitas Muhammadiyah Yogyakarta, 2021)
The high heat transfer rate from the environment to the chilled water pipe will affect the performance of the mini water chiller prototype, so it is necessary to insulate the chilled water pipe using the right insulator to optimize the performance of the mini water chiller prototype. Therefore, this study aims to determine the effect of the chilled water pipe insulator variations: nitrile rubber expanded and polyurethane foam on the optimal temperature and cooling rate of the mini water chiller prototype cabin. The method used in this study is an experimental method with a variation of the insulator as independent variables and the optimal temperature also cooling rate of the mini water chiller prototype cabin as the dependent variables. The testing process was carried out 20 times repetition of data collection on each variation using a stopwatch, thermo gun, thermostat, ampere pliers, a bulb, and a water heating element as a tool in research. In addition, it expanded nitrile rubber and polyurethane foam spray as research material. The results obtained from this study showed that the average optimal temperature achievement of the mini water chiller prototype with polyurethane foam insulator was 11.242◦C, and with the nitrile rubber expanded insulator was 11.250◦C. Otherwise, the average cooling rate of the mini water chiller prototype cabin with polyurethane foam insulator variation was 0.001421◦C, while in the variation of nitrile rubber expanded it was 0.001032◦C, which indicates that there is an effect of chilled water pipe insulator variations on the performance of the mini water chiller prototype.